Tin mining in Myanmar: Production and potential. (December 2015) - Gardiner, Nicholas J.; Sykes, John P.; Trench, Allan; Robb, Laurence J.
Abstract: In 2014, Myanmar (Burma) confounded industry analysts by emerging to become the World's third biggest tin producer, experiencing a 5-year tin production increase of ca. 4900%. This surprise emergence of Myanmar as a major tin producer is a possible Black Swan event that potentially has significant repercussions both for the future of global tin production, and for the economic development of Myanmar. This is a disruptive event that has likely contributed to a substantial drop in tin prices in 2015. The Myanmar production increase came from a new mine site in Wa State, and not from the traditional tin-producing areas in the South. We discuss tin mining and potential in Myanmar and consider whether it could provide a foundation for the economic rehabilitation of the country. Highlights: Until recently tin prices were forecast to increase due to declining mine supply. However, forecasts were hampered by limited information on the developing world. Myanmar surprised analysts by becoming the third largest tin miner in 2014. The supply increase came from a new Myanmar tin mining area in Wa State. We discuss the potential for Myanmar to sustain this supply over the long term.